Acute Pancreatitis and Rhabdomyolysis with Acute Kidney Injury following Multiple Wasp Stings. (19th June 2017) - Yang, Seo Hee; Song, Yeon Han; Kim, Tae Hoon; Kim, Su Bin; Han, Sang Youb; Kim, Han-Seong; Oh, Se Won
Abstract : Multiple wasp stings can induce multiple organ dysfunction by toxic reactions. However, acute pancreatitis is a rare manifestation in wasp sting injury. A 74-year-old woman visited the emergency department by anaphylactic shock because of multiple wasp stings. Acute kidney injury, rhabdomyolysis, hepatotoxicity, and coagulopathy were developed next day. Serum amylase and lipase were elevated and an abdominal computed tomography revealed an acute pancreatitis. Urine output was recovered after 16 days of oliguria (below 500 ml/day). Her kidney, liver, and pancreas injury gradually improved after sessions of renal replacement therapy.